b(8a+7c)-2d(8a+7c)=

Simple and best practice solution for b(8a+7c)-2d(8a+7c)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b(8a+7c)-2d(8a+7c)= equation:


Simplifying
b(8a + 7c) + -2d(8a + 7c) = 0
(8a * b + 7c * b) + -2d(8a + 7c) = 0
(8ab + 7bc) + -2d(8a + 7c) = 0
8ab + 7bc + (8a * -2d + 7c * -2d) = 0
8ab + 7bc + (-16ad + -14cd) = 0

Reorder the terms:
8ab + -16ad + 7bc + -14cd = 0

Solving
8ab + -16ad + 7bc + -14cd = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-7bc' to each side of the equation.
8ab + -16ad + 7bc + -7bc + -14cd = 0 + -7bc

Combine like terms: 7bc + -7bc = 0
8ab + -16ad + 0 + -14cd = 0 + -7bc
8ab + -16ad + -14cd = 0 + -7bc
Remove the zero:
8ab + -16ad + -14cd = -7bc

Add '14cd' to each side of the equation.
8ab + -16ad + -14cd + 14cd = -7bc + 14cd

Combine like terms: -14cd + 14cd = 0
8ab + -16ad + 0 = -7bc + 14cd
8ab + -16ad = -7bc + 14cd

Reorder the terms:
8ab + -16ad + 7bc + -14cd = -7bc + 7bc + 14cd + -14cd

Combine like terms: -7bc + 7bc = 0
8ab + -16ad + 7bc + -14cd = 0 + 14cd + -14cd
8ab + -16ad + 7bc + -14cd = 14cd + -14cd

Combine like terms: 14cd + -14cd = 0
8ab + -16ad + 7bc + -14cd = 0

The solution to this equation could not be determined.

See similar equations:

| 13x-12y+14z=12y+14z+48x | | (3h-4)(2h+3)=(3h-2)(2h+1) | | 5log(3x-2)=3 | | x^3+2x^3=5 | | 3x+4y+7z=12 | | 3-2lnx=6 | | (4+y)(3y-8)=0 | | 7/2-9(-1)/2 | | 12/3(x=3)=1 | | 3y=5x-(1) | | 4(x-4)-8x=4 | | 3x-4+-2x=-5+5x | | 9x=3+7x | | x:17=2 | | 16x+8y+40x= | | y=-0.60*45+141 | | y=-0.60*35+141 | | 8+5x=-20+x | | x^2-12x-1=-3 | | y=-0.60*25+141 | | 6=5(x+2)-7x | | ln(t)-2= | | 1xY-60xX= | | 13Y-12X+14Z=12Y+14Z+48X | | -5x+2y+z= | | 5x+2y-z= | | 15x^2+10x-9=0 | | 2(5)=16-(-6) | | -49=2x+3x+6 | | X+7=14X+7-7 | | 145-342=2 | | 6x+7-7x=3 |

Equations solver categories